Effect of altitudinal variations on biological activities of Justicia adhatoda L. growing wildly in Western Himalayas: An in vitro assessment - Mehak Jamwal, Sunil Puri, Radha, Niharika Sharma, Suraj Prakash, Vijay Kumar, Shalini Sharma, Kamlesh, Neeraj Kumari, Ashok Pundir, Daljeet Singh (Journal of Applied Pharmaceutical Science, 2022)
An investigation was carried out to check the influence of altitude on antibacterial, antifungal, anti-inflammatory, and antioxidant activities displayed by ethanolic leaf extracts of Justicia adhatoda L. Justicia adhatoda is a medicinal plant, growing predominantly at an altitude of 1,300 m above sea level. The collections of leaves were made from plants growing across different altitudinal ranges. The antibacterial activity was tested against four different bacterial strains, namely Escherichia coli (MTCC 82), Staphylococcus aureus (MTCC 96), Pseudomonas aeruginosa (MTCC 2453), and Klebsiella pneumonia (MTCC 39) by disk diffusion assay and subsequently antifungal activity was tested on Rosellinia necatrix (HG964402.1) and Fusarium spp. (SR266-9) by poisoned food technique. The leaf extracts exhibited a potent inhibitory effect on the tested bacterial and fungal strains. Consequently, the antioxidant activity was found to be significantly higher among the extracts from high altitudes, whereas the difference observed in antibacterial, antifungal, and anti-inflammatory activities is not statistically significant. The extracts were further characterized by GC–MS analysis and the presence of pharmacologically important compounds, viz. 1-hexyl-2- nitrocyclohexane, 2-naphthalenamine, 1-butanol, 3-methyl-, acetate, and 1-docosene, were reported.
Keywords: Justicia adhatoda L., altitude, variation, medicinal, antimicrobial, anti-inflammatory, antioxidant